Evolving Treatments for Acute Ischemic Stroke. Issue 9 (29th April 2016) - Zerna, Charlotte; Hegedus, Janka; Hill, Michael D.
Abstract : The purpose of this article is to review advances in stroke treatment in the hyperacute period. With recent evolutions of technology in the fields of imaging, thrombectomy devices, and emergency room workflow management, as well as improvement in statistical methods and study design, there have been ground breaking changes in the treatment of acute ischemic stroke. We describe how stroke presents as a clinical syndrome and how imaging as the most important biomarker will help differentiate between stroke subtypes and treatment eligibility. The evolution of hyperacute treatment has led to the current standard of care: intravenous thrombolysis with tissue-type plasminogen activator and endovascular treatment for proximal vessel occlusion in the anterior cerebral circulation. All patients with acute ischemic stroke are in need of hyperacute secondary prevention because the risk of recurrence is highest closest to the index event. The dominant themes of modern stroke care are the use of neurovascular imaging and speed of diagnosis and treatment.